2023
DOI: 10.1590/1806-9282.20221436
|View full text |Cite
|
Sign up to set email alerts
|

Lung and physical function in post COVID-19 and clinical and functional associations: a cross-sectional study in Brazil

Abstract: OBJECTIVE:The purpose of this study was to assess exercise capacity, lung and physical function in COVID-19 survivors, and the association of lesion-level characteristics assessed by chest computed tomography, probable sarcopenia, and percentage of diffusing capacity of the lung for carbon monoxide with clinical and functional variables. METHODS: This study was conducted in Salvador, Bahia, Brazil. All patients had a laboratory-confirmed SARS-CoV-2 infection. The sociodemographic characteristics, COVID-19 expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…These authors also noted that hospitalization was associated with worse muscle strength and reduced DLCO. It is worth noting that, unlike our study, the studies by Clavario et al 37 and Nascimento et al 38 were performed at a very early stage of long COVID, which reinforces the importance of continuing to monitor muscle function in the long term.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These authors also noted that hospitalization was associated with worse muscle strength and reduced DLCO. It is worth noting that, unlike our study, the studies by Clavario et al 37 and Nascimento et al 38 were performed at a very early stage of long COVID, which reinforces the importance of continuing to monitor muscle function in the long term.…”
Section: Discussionsupporting
confidence: 66%
“…Based on the finding that muscle strength was independently associated with performance during the exercise, the authors concluded that muscle impairment may be responsible for most of the functional decrease. The relationship between reduced muscle strength and poor exercise performance was also noted by Nascimento et al 38 , in which a probable diagnosis of sarcopenia was associated with worse functional capacity on exertion according to the 6-min walking distance. These authors also noted that hospitalization was associated with worse muscle strength and reduced DLCO.…”
Section: Discussionsupporting
confidence: 63%
“…We would like to share our ideas on the article entitled “Lung and physical function in post COVID-19 and clinical and functional associations: a cross-sectional study in Brazil 1 ”. Nascimento et al 1 investigated the relationship between lesion-level characteristics assessed by chest computed tomography, probable sarcopenia, and the percentage of diffusing capacity of the lung for carbon monoxide with clinical and functional variables in COVID-19 survivors 1 . Muscle impairment and lung dysfunction are widespread in COVID-19 survivors, according to Nascimento et al 1 and hospitalization was related to the worst muscle force and carbon monoxide diffusing capacity of the lung 1 .…”
mentioning
confidence: 99%
“…Nascimento et al 1 investigated the relationship between lesion-level characteristics assessed by chest computed tomography, probable sarcopenia, and the percentage of diffusing capacity of the lung for carbon monoxide with clinical and functional variables in COVID-19 survivors 1 . Muscle impairment and lung dysfunction are widespread in COVID-19 survivors, according to Nascimento et al 1 and hospitalization was related to the worst muscle force and carbon monoxide diffusing capacity of the lung 1 . According to Nascimento et al 1 the findings underscore the need for long-term follow-up of such patients as well as rehabilitation programs 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation